Beyond geometry : experiments in form, 1940s-70 - Zelevansky, Lynn; Blanc, Aleca Le; Zelevansky, Lynn; Hillings L., Valerie; Peternák, Miklós; LaBelle, Brandon; Frank, Peter; Katzenstein, Inés; Hillings, Valerie L.; Peternak, Milklos; LaBelle, Brandon (Cambridge, Massachusetts : the MIT Press, 2004)
Albers, Josef ; Alexander, Peter ; Andre, Carl ; Antin, Eleanor ; Arden Quin, Carmelo ; Asher, Michael ; Azeredo, Ronaldo ; Baer, Jo ; Baldessari, John ; Baljeu, Joost ; Barré, Martin ; Barry, Robert ; Becher, Bernd & Hilla ; Bell, Larry ; Belloli, Carlo ; Benjamin, Karl ; Bill, Max ; Bochner, Mel ; Breer, Robert ; Buren, Daniel ; Burkhardt, Klaus ; Bury, Pol ; Caldas, Waltercio ; de Camargo, Sergio ; Camnitzer, Luis ; de Campos, Augusto ; Carson, Karen ; Carvão, Aluisio ; Castellani, Enrico ; Charlton, Alan ; Clark, Lygia ; Colares, Raimundo ; Colombo, Gianni ; Cruz-Diez, Carlos ; Dadamaino ; Darboven, Hanne ; Dekkers, Ad ; Dias, Antonio ; Dibbets, Jan ; Diller, Burgoyne ; Drozdz, Stanislaw ; Espinosa, Manuel ; Fahlström, Öyvind ; Fangor, Wojciech ; Riverhead (New York) ; Fontana, Lucio ; Gego ; Goeritz, Mathias ; Gomringer, Eugen ; Graeser, Camille ; Graham, Dan ; Grygar, Milan ; Gysin, Brion ; Haacke, Hans ; Havel, Václav ; Hendricks, Bici ; Hesse, Eva ; Horwitz, Channa ; Huebler, Douglas ; Irwin, Robert ; Judd, Donald ; Kawara, On ; Kelly, Ellsworth ; Knifer, Julije ; Kosice, Gyula ; Kostelanetz, Richard ; Kosuth, Joseph ; Kozlowski, Jaroslaw ; Kusama Yayoi ; Lamelas, David ; LeWitt, Sol ; Loewensberg, Verena ; Lohse, Richard Paul ; Lozza, Raul ; Mack, Heinz ; Maldonado, Tomàs ; Mangold, Robert ; Manuel da Silva Oliveira, Antonio ; Manzoni, Piero ; de Maria, Walter ; Martin, Agnes ; McCracken, John ; McLaughlin, John ; Meireles, Cildo ; Mele, Juan ; Morellet, François ; Morris, Robert ; Munari, Bruno ; Nauman, Bruce ; Newman, Barnett ; Nogueira Lima, Mauricio ; Nordman, Maria ; Novak, Ladislav ; Oiticica, Hélio ; Opalka, Roman ; Oppenheim, Dennis ; Palermo, Blinky ; Paolini, Giulio ; Pape, Lygia ; Parc, Julio Le ; Piene, Otto ; etc.
Exhibition. Beyond Geometry : Experiments in Form, 1940s-1970s (2). LACMA (Los Angeles County Museum of Art) Los Angeles. Miami Art Museum Miami. 2004-06-13. 2004-11-18. 2003-10-03. 2004-05-01
boek